Taming the presumption of innocence - Lippke, Richard L., 1954- (New York, NY : Oxford University Press, 2016)
Taming the Presumption of Innocence provides a comprehensive account of the presumption of innocence in criminal law and procedure. It maintains that the presumption is a vital component of the proof structure of criminal trials.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on January 28, 2016).
Keywords: Presumptions (Law); Presumption of innocence; Law